Civil Law: Inheritance Law According To The Civil Code - Sulistyani Eka Lestari (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
Inheritance law is an important part of civil law that regulates the transfer of a person's assets after death to their heirs. In the Indonesian legal system, there are three applicable inheritance laws: Western civil inheritance law (KUHPerdata), Islamic inheritance law, and customary inheritance law. This article discusses inheritance law according toCivil Code(Civil Code) which is a legacy of Dutch law and is still in effect today. Research purposesThis study aims to analyze the inheritance law provisions in the Civil Code, explain the applicable inheritance principles and principles, and outline the status of heirs and the inheritance distribution mechanism based on positive law provisions. This research is expected to contribute to the development of civil law and serve as a reference in the practice of resolving inheritance disputes in Indonesia.This study uses a normative approach by analyzing provisions in the Civil Code and legal doctrines from experts. The analysis shows that the civil inheritance law system emphasizes the principles of individualism, freedom of will, and protection of the rights of certain heirs through legitimate institutions.